2007
DOI: 10.3989/gya.2007.v58.i4.444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on microbiological and oil properties of black cumin (<i>Nigella sativa</i> L.)

Abstract: RESUMENEfecto de la radiación gamma sobre la microbiología y las propiedaddes del aceite del comino negro (Nigella sativa L.)Muestras de comino negro adquiridas en el mercado fueron irradiadas a dosis de 2.5 kGy, 6 kGy, 8 kGy y 10 kGy, respectivamente. Coincidiendo con el aumento en la dosis de irradiación, se incrementaron tanto la acidez libre, como el índice de peróxidos de las muestras, mientras que se redujeron en el aceite el índice de yodo, el índice de refracción y la resistencia a la oxidación medida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 9 publications
8
38
0
2
Order By: Relevance
“…After 6 months of storage, only 9 kGy signifi cantly (p < 0.01) decreased the total acidity, while after 12 months of storage, both irradiation doses 6 and 9 kGy significantly (p < 0.01) increased the total acidity in peanut seeds. This fi nding is consistent with work carried out by other researchers who studied the eff ect of irradiation with doses up to 10 kGy on other oil seeds (black cumin seeds; Arici et al, 2007). However, on other hand, Wen et al (2006) found no signifi cant changes in pH and acidity following 4 and 8 kGy gamma irradiation in lucium fruit.…”
Section: Eff Ect Of Gamma Irradiation and Storage Time On Chemical Prsupporting
confidence: 81%
“…After 6 months of storage, only 9 kGy signifi cantly (p < 0.01) decreased the total acidity, while after 12 months of storage, both irradiation doses 6 and 9 kGy significantly (p < 0.01) increased the total acidity in peanut seeds. This fi nding is consistent with work carried out by other researchers who studied the eff ect of irradiation with doses up to 10 kGy on other oil seeds (black cumin seeds; Arici et al, 2007). However, on other hand, Wen et al (2006) found no signifi cant changes in pH and acidity following 4 and 8 kGy gamma irradiation in lucium fruit.…”
Section: Eff Ect Of Gamma Irradiation and Storage Time On Chemical Prsupporting
confidence: 81%
“…The decrease in the unsaturated fatty acid content and the concomitant increase in the saturated fatty acid content are explained by De Camargo et al [10], who stated that the ratio of the oxidation rates of stearic, oleic, linoleic and linolenic acids was 1: 10: 100: 200. Another study suggested that, the decrease in unsaturated fatty acids during oil storage is mainly due to a molecular structure change in fatty acids [38]. …”
Section: Effects Of Storage Times On Fatty Acid Content Of Sesame Sunmentioning
confidence: 99%
“…Quality requirements demand enhanced conservation techniques for chestnuts and related products. In this context, decontamination methods based on high-energy electrons or γ-rays irradiation are being studied as alternatives; Arici et al (2007) irradiated black cumin with 2.5 to 10 kGy for the purpose of microorganism's elimination, while studying the effects on physico-chemical properties and on fatty acids profile. Irradiation beneficial effects include reduction of storage losses, shelf life extension, and improvement of microbiological and parasitological safety of foods, while being safe to the environment.…”
Section: Introductionmentioning
confidence: 99%